The Vietnam War from the Rear Echelon : An Intelligence Officer's Memoir, 1972-1973 - Lomperis, Timothy J., 1947- (Book collections on Project MUSE., 2011)
This incisive memoir is essential for better comprehending what the Vietnam experience was like for the large contingent of Americans who served there. It suggests the need for some fundamental rethinking about Vietnam--not only for the war's veterans but also for those concerned with the lessons it carries for U.S. involvement in current insurgencies.